The survival strategies used by Bustop TV and Magamba TV in Zimbabwe’s uncertain media landscape - Mhlanga, Brian P. (Midlands State University, 2018)
The study investigates survival strategies of Bustop TV and Magamba TV in Zimbabwe’s uncertain media landscape. The study is situated in a conceptual framework that looks into revenue models such as the dual-product marketplace and advertising revenue model. It makes use of the qualitative paradigm with a focus on case study. In-depth interviews were used as methods of data collection. The online media organisations like the traditional media organisations depend on revenue models like dual product market place and advertising revenue model. However the research revealed that for online organisations to survive they need to make use of alternative sources of revenue.